2003
DOI: 10.1046/j.1365-2923.37.s1.3.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of a simulation examination using a high-fidelity child manikin

Abstract: With a carefully designed rating instrument and simulation operation, the manikin-based simulation examination was shown to be reliable and valid. However, a further refinement of the test instrument will be required for higher stake examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…Although some studies have shown validity of the use of high‐fidelity mannequin in the assessment process, 14,15 their results are not translatable to our study because of the differences in methodology and scoring technique. Larger studies are required to conclusively prove validity than just mere pilot studies.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Although some studies have shown validity of the use of high‐fidelity mannequin in the assessment process, 14,15 their results are not translatable to our study because of the differences in methodology and scoring technique. Larger studies are required to conclusively prove validity than just mere pilot studies.…”
Section: Discussionmentioning
confidence: 77%
“…High‐fidelity mannequins have potential advantages as educational tools 10,11 or assessment tools 12–14 . This is a pilot study specifically looking at the use of high‐ vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on a global evaluation system rated independently by several evaluators are both reliable and valid. In particular, the validity has repeatedly been shown for use of a patient simulator as a performance evaluation tool [3,6,8,[10][11][12][13]. This highlights the appropriateness and worth of simulation training to critical care training in general.…”
Section: Discussionmentioning
confidence: 90%
“…The authors went further, to comment that simulation would be a useful tool to overcome some of these deficiencies for individuals and teams. In another paediatric study [15], residents took part in high-fidelity child manikin-based simulation. The study assessed resident performances, examining the validity and reliability of the process.…”
Section: Simulation In Postgraduate Educationmentioning
confidence: 99%